1958
DOI: 10.1113/jphysiol.1958.sp006117
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of histamine and 5‐hydroxytryptamine to anaphylactic shock in different species

Abstract: Histamine is released during anaphylactic shock and accounts for many of the observed symptoms. In recent years, interest has been focused on 5-hydroxytryptamine (5-HT) as another amine involved in the anaphylactic reaction. The present study was undertaken to assess the relative importance of histamine and 5-HT in anaphylactic shock in different species. The rat is particularly suitable for this work as its tissues can be preferentially depleted of either of these amines (Parratt & West, 1957 b) and severe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

1960
1960
1995
1995

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…In such situa tions, a number of vasoactive substances have been found to be released in addition to prostaglandins, histamine and serotonin, e.g. slow-reacting substance, kinins, lysosomal enzymes and adrenal catecholamines [6,7,9,17,39,42,43]. Any of these may have contributed to the circulatory changes observed after injection of ALG.…”
Section: Discussionmentioning
confidence: 99%
“…In such situa tions, a number of vasoactive substances have been found to be released in addition to prostaglandins, histamine and serotonin, e.g. slow-reacting substance, kinins, lysosomal enzymes and adrenal catecholamines [6,7,9,17,39,42,43]. Any of these may have contributed to the circulatory changes observed after injection of ALG.…”
Section: Discussionmentioning
confidence: 99%
“…One of these, namely UML-491, has since been shown to antagonise the affects of compound 48/80 in man (3) and to improve patients suffering from resistant migraine of long standing (4,5). It was of interest therefore to study further some properties of these derivatives, especially as serotonin and histamine probably participate in allergic and anaphylactic pheno mena (6,7,8,9,10).…”
mentioning
confidence: 99%
“…The precipitin reaction in vitro is also similarly unaffected by the presence of heparin. It was reported before (13) and now again it has been confirmed that in this species there is a rise in lung histamine content during anaphylaxis. This rise has been accounted for by trapping of leucocytes and platelets in the lung field.…”
Section: Discussionmentioning
confidence: 62%